Interpreting the 35 year SBUV PMC record with SOFIE observations. Issue 22 (18th November 2014) - Hervig, Mark E.; Stevens, Michael H.
Abstract: Observations of polar mesospheric clouds (PMC) from the solar backscatter ultraviolet (SBUV) instruments are compared to the Solar Occultation For Ice Experiment (SOFIE). SBUV measurements are used to determine the PMC vertical column ice mass abundance (or ice water content, IWC) for comparison with SOFIE. Improved SBUV simulations are employed that accounted for nonspherical particles, and the multiwavelength measurements are used to retrieve particle size as the median radius ( rm ) of a Gaussian distribution. SBUV IWC retrievals incorporated rm as temporally smoothed values, to reduce propagation of rm errors but capture the effects of variable rm in IWC. For seasonal averages the SBUV‐SOFIE rm differences are 22 ± 6% in the Northern Hemisphere (NH) and 22 ± 12% in the Southern Hemisphere (SH), and IWC differences were 3 ± 6% in the NH and 7 ± 12% in the SH. The SBUV record was used to derive IWC and particle size for 1979–2013 for 64–74°N. The results indicate a secular increase in rm of 0.23 ± 0.16 nm decade −1 and a linear IWC trend of 2.6 ± 1.2% decade −1 . Multiple regression of IWC to solar and trend terms reveals that 1.6% decade −1 of the IWC trend can be attributed to a decline in solar Lyman α since 1979. The residual IWC trend from multiple regression (1.0% decade −1 ), presumably due to other external forcing such as changing atmospheric composition, is a factor of six less than PMC trends previously reported from a shorter time series of SBUV data. Key Points: SBUV retrievals of PMC ice mass and particle size for nonspherical particles SBUV and SOFIE are in good agreement on PMC mass and size Roughly half of PMC trend is attributed to lower solar flux since 1979